Otimização de um condicionador de ar do tipo split com vazão variável de refrigerante - Brochier, Felipe Osmar Berwanger (Universidade do Vale do Rio dos Sinos, 2014)
This work aims to optimize the operational cost of an air conditioning system with variable refrigerant flow (VRF). The cost is dependent of the following parameters: condenser air flow, number of condenser fins and circuits, compressor frequency and the expansion device. The optimization considered the frequencies of occurrence of four distinct ambient temperatures in the city of Porto Alegre. The air conditioner presented in this work exchange heat using a single stage vapor compression cycle, with the refrigerant R-410A as the working fluid. The complete system comprises a compressor, a condenser, an evaporator and a capillary tube and was analytically modeled using the EES (Engineering Equation Solver) software. The parameters were fitted according to results obtained in a calorimeter and for optimization, a genetic algorithm was programmed using the same software. After the optimization of the operational cost as a function of the project parameters, the COP was raised up to 12% in external ambient air at 35 °C. The optimization of the operational cost as a function of the control parameters showed even a more significant system COP raise. A comparison between the COP of a constant air and refrigerant flow system and a variable air and refrigerant flow system was also performed.
Keywords: Modeling; Optimization; Genetic algorithm; VRF; Modelamento; Otimização; Algoritmo genético; VRV; R-410A; ACCNPQ::Engenharias::Engenharia Mecânica